2019
DOI: 10.1111/add.14579
|View full text |Cite
|
Sign up to set email alerts
|

Rules about smoking and vaping in the home: findings from the 2016 International Tobacco Control Four Country Smoking and Vaping Survey

Abstract: Aims To examine rules about smoking and vaping in the home in relation to beliefs about the relative harm of secondhand vapor (SHV) compared with second-hand smoke (SHS) in four countries: Canada, United States, England and Australia. Design Data were available from 12 294 adults (18+) who participated in the 2016 (wave 1) International Tobacco Control Four Country Smoking and Vaping (ITC 4CV1) Survey. Participants All participants were current or recent former adult smokers. Measurements Data were analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The prevalence of strict home smoking bans in the current report (42.0%) was lower than prior studies’ prevalence, with the enforcement of voluntary strict home smoking bans reported to be 61% in homes in Italy 38 , 50% in homes in the United States 35 , and 66.1% in homes in Poland 39 . Similarly, a study based on data from four countries, namely, Canada (67.8%), the United States (60.2%), England (59.2%), and Australia (66.2%), reported higher prevalence of strict home smoking bans than our study 40 . In addition, a study in Spain found that approximately 57.4% of households had complete indoor smoke-free rules 41 .…”
Section: Discussionsupporting
confidence: 72%
“…The prevalence of strict home smoking bans in the current report (42.0%) was lower than prior studies’ prevalence, with the enforcement of voluntary strict home smoking bans reported to be 61% in homes in Italy 38 , 50% in homes in the United States 35 , and 66.1% in homes in Poland 39 . Similarly, a study based on data from four countries, namely, Canada (67.8%), the United States (60.2%), England (59.2%), and Australia (66.2%), reported higher prevalence of strict home smoking bans than our study 40 . In addition, a study in Spain found that approximately 57.4% of households had complete indoor smoke-free rules 41 .…”
Section: Discussionsupporting
confidence: 72%
“…The existence of these rules was 54.8% in the whole population. In the previous studies, it was found to be 42% in Kuwait, 59.2% in England, 60.2% in the United States, 67.8% in Canada and 66.2% in Australia (19,21). The diversity of rules prohibiting tobacco use may be related to the level of development, cultural differences and health literacy of countries.…”
Section: Discussionmentioning
confidence: 94%
“…4 5 In a recent survey, smoking inside the home was allowed in 37.4% of homes of current and former smokers, while vaping inside the home was allowed in 60.4% of homes of vapers, as secondhand nicotine vape exposure was perceived to be less harmful than secondhand smoking. 6 Although secondhand exposure to particulate matter from e-cigarettes is lower than from combustible cigarettes, 7 the ultrafine particle concentration in e-cigarette aerosol can be higher than in cigarette smoke, potentially delivering toxins to the distal airways and alveoli. 8 E-cigarette aerosol also contains volatile aldehydes and oxidant metals, [9][10][11][12][13][14] compounds that are known to cause lung toxicity.…”
Section: Introductionmentioning
confidence: 99%